Astrocyte-induced firing in primary afferent axons - Fanny Gaudel; Julia Giraud; Philippe Morquette; Marc Couillard-Larocque; Dorly Verdier; Arlette Kolta (iScience)
Summary: The large-caliber primary afferents innervating the spindles of the jaw-closing muscles have their cell bodies located centrally in the mesencephalic trigeminal nucleus (NVmes). We have shown, in an acid-induced jaw muscle chronic myalgia model, that these afferents exhibit increased excitability and ectopic discharges that emerge from subthreshold membrane oscillations (SMOs) supported by a persistent sodium current (INaP) exquisitely sensitive to extracellular Ca2+-decreases. Here, we explore if the Ca2+-binding astrocytic protein, S100β, contributes to this hyperexcitability emergence and aim to localize the site where ectopic discharge arises using whole-cell patch-clamp recordings on mice brain slices. We found that astrocytes, by lowering [Ca2+]e at focal points along the axons of NVmes neurons through S100β, enhance the amplitude of the NaV1.6-dependent SMOs, leading to ectopic firing. These findings suggest a crucial role for astrocytes in excitability regulation and raise questions about this neuron-astrocyte interaction as a key contributor to hyperexcitability in several pathologies.